Ethics in Public Health Research and Clinical Research - Khan, Muhammad Waseem; Tareen, Afrasiab Khan; Sultan, Imrana Niaz (Bangladesh Journal of Bioethics, 2016)
Research conducted with ethical values is the need of modern world and great benefit to the society in general and human beings in particular. Clinical research basically focuses on improving human health individually by improving current trends, methodologies and identifying innovative methods of treatment. Public health research is mainly concerned with the health of the entire populace. No standard rules can be formulated for conducting any form of research ethically; however following some basic ethical values can assure ethical conduct of research. In any research study whether that is public health research or clinical research, the importance is need to be to recognize an ethical standard that respects individuals autonomy and communitys wellbeing. Ethical values in research studies can be achieved by requiring individuals and communitys collective collaboration for the protection of individuals autonomy, dignity and wellbeing.